Exploring for Self-Care Process in Patients with Parkinson\'s Disease: a Grounded Theory Study - Mohammad Ali Soleimani; Reza Negarandeh; Farideh Bastani (Tehran University of Medical Sciences, 2015)
Background & Aim: The ultimate goal of self-care behavior is patientschr('39') empowerment. There are limited studies on perspectives of patients with Parkinsonchr('39')s disease on self-care. This study aimed to explore for the process of self-care in patients with Parkinson's disease during 2011 to 2013 .   Methods & Materials: This exploratory qualitative study was carried out using grounded theory method. Data were collected via semi-structured in-depth interviews and field notes. We interviewed with 12 patients with Parkinson chr('39')s disease and four family caregivers . Participants were selected from two neurology clinics. Interviews were conducted at participantschr('39') homes or nursing homes. Data were analyzed using the Corbin and Strauss (2008) approach .    Results: Concepts of study were identified using a micro and general analysis. The chr('39')fear of becoming crippledchr('39') was identified as a main concern. Strategies used in response to context included chr('39')independencychr('39'), chr('39')spiritual carechr('39'), chr('39')informed self-carechr('39') and 'seeking treatment'. chr('39')Striving for taking independent self-carechr('39') was the most important process. Demographic, familial and social factors had important roles in self-care processes of patients with Parkinsonchr('39')s disease .   Conclusion: The process of self-care in patients with Parkinson's disease depends on the context and severity of the signs and symptoms. Health care providers especially nurses can support patients with Parkinsonchr('39')s disease in achieving maintain independence in self-care. In addition, attention to self-care behaviors with focus on person as self-care agent can considerably increase control and management of life .